2010
DOI: 10.1111/j.1365-2958.2010.07338.x
|View full text |Cite
|
Sign up to set email alerts
|

Genes essential for morphological development and antibiotic production in Streptomyces coelicolor are targets of BldD during vegetative growth

Abstract: SummaryBldD is a transcriptional regulator essential for morphological development and antibiotic production in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
261
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(276 citation statements)
references
References 84 publications
8
261
1
Order By: Relevance
“…The master regulators in the whi family, which are believed crucial for sporulation of aerial hyphae, have also been identified in the core genome: WhiG (strep4938) which encodes a sigma factor; WhiH (strep5046) which encodes a repressor; WhiI (strep5113) which encodes a two-component regulator; WhiA (strep3138), WhiB (strep3685) and WhiD (strep4478). Two other sigma factors that are important for sporulation, BldD (strep2821) [62] and SigF (strep4128) [63] are also present in the core genome [26]. …”
Section: Resultsmentioning
confidence: 99%
“…The master regulators in the whi family, which are believed crucial for sporulation of aerial hyphae, have also been identified in the core genome: WhiG (strep4938) which encodes a sigma factor; WhiH (strep5046) which encodes a repressor; WhiI (strep5113) which encodes a two-component regulator; WhiA (strep3138), WhiB (strep3685) and WhiD (strep4478). Two other sigma factors that are important for sporulation, BldD (strep2821) [62] and SigF (strep4128) [63] are also present in the core genome [26]. …”
Section: Resultsmentioning
confidence: 99%
“…Following early genomic analyses predicting that GGDEF, EAL, and HD-GYP domains are involved in c-di-GMP metabolism in a variety of bacteria (27,34,107), experimental evidence for c-di-GMP signaling pathways was obtained for the major phylogenetic branches, including the Proteobacteria, Spirochetes, Cyanobacteria, Deinococcus-Thermus, Thermotogae, Actinobacteria, and Firmicutes (59,181,182). In the past several years, genome sequencing has revealed domains associated with c-di-GMP signaling even in the phyla previously thought to be devoid of c-di-GMP.…”
Section: Cyclic Di-gmp In Genomic Context Cyclic Di-gmp Signaling Enzmentioning
confidence: 99%
“…These hyphae undergo a sporulation-like cell division process, resulting in an aerial mycelium comprised of prespores, each of which contains only one set of genomic DNA, that subsequently metamorphose into mature spores (322). den Hengst et al first discovered that overexpression of the DGC designated CdgA (SCO2817) blocks formation of aerial hyphae and results in a bald colony appearance (182). Overexpression of yet another DGC, CdgB (SCO4281), resulted in the impaired formation of aerial mycelium.…”
Section: Regulation Of Cell Cycle and Differentiationmentioning
confidence: 99%
“…5 The bldD gene product, BldD, is a small DNA-binding protein with 167 amino acids and exists predominantly as a homodimer in solution. [6][7][8] BldD binds its own promoter and regulatory regions of several genes, 6,7,9,10 including bldN encoding a sigma factor involved in aerial hyphae formation, 11 whiG encoding a sigma factor related in spore formation 12 and sigH encoding a sigma factor associated with stress responses. 13 The transcription levels of these target genes in the bldD mutant in comparison with those of the wild type have shown that BldD operates as a transcriptional repressor.…”
Section: Introductionmentioning
confidence: 99%
“…13 The transcription levels of these target genes in the bldD mutant in comparison with those of the wild type have shown that BldD operates as a transcriptional repressor. 9,10,13 BldD has two structurally independent domains, an N-terminal domain (residues 1-79, BldD-NTD), which is responsible for both the DNA-binding and dimerization, and a C-terminal domain (residues 80-167, BldD-CTD), of which function is unknown. 8 Although the crystal structure of BldD-NTD showed a classical helix-turn-helix motif for DNA binding and a remarked structural similarity with lambda repressor, 14 it was not sufficient to fully explain the regulatory mechanism of BldD, without structural information of the BldD-CTD.…”
Section: Introductionmentioning
confidence: 99%